2023
DOI: 10.3390/ijms241310910
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking the Deceptive Nature of Cancer Stem Cells: The Role of CD133 in Revealing Their Secrets

Julia Pospieszna,
Hanna Dams-Kozlowska,
Wachirawit Udomsak
et al.

Abstract: Cancer remains a leading cause of death globally, and its complexity poses a significant challenge to effective treatment. Cancer stem cells and their markers have become key players in tumor growth and progression. CD133, a marker in various cancer types, is an active research area as a potential therapeutic target. This article explores the role of CD133 in cancer treatment, beginning with an overview of cancer statistics and an explanation of cancer stem cells and their markers. The rise of CD133 is discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 227 publications
0
3
0
Order By: Relevance
“…CD133 (also known as prominin-1 and AC133) has been identified as a surface marker of cancer stem cells (CSCs) in an increasing number of investigations and has been detected in various solid tumors, including ovarian cancer [12,13]. Our earlier analysis demonstrated that CD133 is involved in the carcinogenesis of serous ovarian cancer, with dynamically elevated expression in high-grade serous carcinoma entities [14].…”
Section: Cd133 Cd47 and Pd-l1 Expression In Ovarian High-grade Serous...mentioning
confidence: 99%
“…CD133 (also known as prominin-1 and AC133) has been identified as a surface marker of cancer stem cells (CSCs) in an increasing number of investigations and has been detected in various solid tumors, including ovarian cancer [12,13]. Our earlier analysis demonstrated that CD133 is involved in the carcinogenesis of serous ovarian cancer, with dynamically elevated expression in high-grade serous carcinoma entities [14].…”
Section: Cd133 Cd47 and Pd-l1 Expression In Ovarian High-grade Serous...mentioning
confidence: 99%
“…The role of CD133 in tumor progression is further evidenced by the results of the preclinical and clinical studies of antitumor drugs targeting the CD133 molecule (for more information, see reviews [110,111]). Such approaches include delivery systems for conventional chemotherapy drugs, as well as drugs that activate the cytotoxic mechanisms of the immune system.…”
Section: Cd133 As a Target Of Therapies Aimed To Eliminate The Most M...mentioning
confidence: 99%
“…The ongoing interest in the CD133 molecule is due to its strong association with the phenotypes of stem and progenitor cells, including cancer stem cells, which are responsible for tumor relapses and metastasis [ 1 , 2 ]. In this regard, CD133 is often considered as a potential prognostic biomarker for various oncological diseases, as well as a promising target for cancer therapy [ 3 , 4 ]. The association of CD133 with cancer progression and poor prognosis was shown in meta-analyses devoted to such malignancies as breast cancer [ 5 ], colorectal cancer [ 6 , 7 , 8 , 9 ], gastric cancer [ 10 , 11 ], glioma [ 12 , 13 , 14 ], head and neck squamous cell carcinoma [ 15 ], hepatocellular carcinoma [ 16 , 17 , 18 ], non-small cell lung cancer [ 19 , 20 , 21 ], osteosarcoma [ 22 ], ovarian cancer [ 23 , 24 ] and pancreatic ductal adenocarcinoma [ 25 ].…”
Section: Introductionmentioning
confidence: 99%